Mechanism Analysis of LINC00665 and Its Peptides CIP2A-BP in Hepatocellular Carcinoma - Li, Yi-Ran; Zong, Rui-Qing; Zhang, Hong-Yan; Meng, Xiao-Yan; Wu, Fei-Xiang (Frontiers in Genetics, 2022)
Background: More and more studies show long non-coding RNAs (lncRNAs) have miniature open reading frames that can be translated into short peptides. Here, we identify the long non-coding gene LINC00665 and its short peptides (CIP2A-BP) in hepatocellular carcinoma (HCC), and explore how they contribute to HCC progression. Materials and methods: First, GSE101728 data were acquired through the Gene Expression Omnibus for identification of differentially expressed genes (DEGs), and Gene Set Enrichment Analysis (GSEA) analysis was conducted to find enriched biological pathways. Then, further bioinformatics analysis was carried out on the screened long non-coding genes, LINC00665 expression was detected in HCC and normal liver samples. The relations among LINC00665 expression, HCC prognosis and clinical characteristics were studied. Receiver operating characteristic (ROC) analysis was also applied to verify the LINC00665 prediction in HCC prognosis. Besides, pertinent experiments on LINC00665 and CIP2A-BP were also carried out to explore their roles in the progression of HCC. Results: As a result, we screened out 332 DEGs in total, including 130 up-regulated and 202 down-regulated DEGs. These DEGs were mainly enriched in Posttranscriptional regulation of gene expression, RNA processing, Nucleolus and Gene silencing biological pathways. In addition, we found that LINC00665 was increased in HCC samples, and substantially indicated its poor prognosis. Compared with normal tissues, LINC00665 had higher expression in the pathological stage III and IV, Tumor free group, people no more than 60 years old, stage T3 & T4, N0 & N1, and M1. ROC curve indicated the variable INC00665 had a certain accuracy in predicting overall survival (OS). Moreover, in functional experiments, LINC00665 knockdown could significantly decrease HCC cell proliferation, migration and invasion, while over-expressed CIP2A-BP could markedly increase HCC cell proliferation, invasion and migration. Conclusion: Our findings not only disclose a unique mechanism by which CIP2A-BP encoded by LINC00665 promotes HCC carcinogenesis, but suggest that these long non-coding genes and short peptides could be used as biomarkers for HCC diagnosis and prognosis and new targets for HCC therapy.